Genetic and functional analyses of TBX4 reveal novel mechanisms underlying pulmonary arterial hypertension. (October 2022) - Yoshida, Yu; Uchida, Keiko; Kodo, Kazuki; Shibata, Hironori; Furutani, Yoshiyuki; Nakayama, Tomotaka; Sakai, Satoshi; Nakanishi, Toshio; Takahashi, Takao; Yamagishi, Hiroyuki
Abstract: Background: Pulmonary arterial hypertension (PAH) is a fatal disease, with approximately 10% of cases associated with genetic variants. Recent genetic studies have reported pathogenic variants in the TBX4 gene in patients with PAH, especially in patients with childhood-onset of the disease, but the pathogenesis of PAH caused by TBX4 variant has not been fully uncovered. Methods: We analysed the TBX4 gene in 75 Japanese patients with sporadic or familial PAH using a PCR-based bidirectional sequencing method. Detected variants were evaluated using in silico analyses as well as in vitro analyses including luciferase assay, immunocytochemistry and chromatin immunoprecipitation (ChIP) whether they have altered function. We also analysed the function of TBX4 using mouse embryonic lung explants with inhibition of Tbx4 expression. Results: Putative pathogenic variants were detected in three cases (4.0%). Our in vitro functional analyses revealed that TBX4 directly regulates the transcriptional activity of fibroblast growth factor 10 ( FGF10 ), whereas the identified TBX4 variant proteins failed to activate the FGF10 gene because of disruption of nuclear localisation signal or poor DNA-binding affinity. Furthermore, ex vivo inhibition of Tbx4 resulted in insufficiency of lung morphogenesis along with specific downregulation of Tie2 and Kruppel-like factor 4 expression. Conclusion: Our results implicate variants in TBX4 as a genetic cause of PAH in a subset of the Japanese population. Variants in TBX4 may lead to PAH through insufficient lung morphogenesis by disrupting the TBX4-mediated direct regulation of FGF10 signalling and pulmonary vascular endothelial dysfunction involving PAH-related molecules. Graphical abstract: Unlabelled Image Highlights: TBX4 variants are more frequent in children than in adults with PAH. Loss-of-function variants of TBX4 are suggested to cause PAH in vitro and ex vivo . FGF10 is a direct target of TBX4 implicated in PAH with lung maldevelopment. TBX4-FGF10 axis may be a therapeutic target for PAH patients with TBX4 variants. TIE2 and KLF4 regulated by TBX4 may be important for vascular endothelial function.